2013
DOI: 10.1002/adom.201200005
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Lasing Wavelength Coverage of Organic Semiconductor Nanofibers by Periodic Organic–Organic Heteroepitaxy

Abstract: Organic–organic heteropitaxy based on alternating and periodic deposition of para-sexiphenyl and alpha-sexithiophene on muscovite mica enables the fabrication of organic semiconductor nanofibers capable of random lasing with multiband emission and operating in the monomolecular recombination regime at room temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Furthermore, the physical properties associated with organic crystal structures are usually highly anisotropic [7][8][9][10]. This circumstance can be utilized, for instance, by adjusting molecular alignments to optimally absorb photons in OSCs [11] or to enable lasing operation of multilayer nanofibers [12]. Exploring and, consequently, exploiting these structure-property relations are thus necessary steps to achieve economically worthwhile device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the physical properties associated with organic crystal structures are usually highly anisotropic [7][8][9][10]. This circumstance can be utilized, for instance, by adjusting molecular alignments to optimally absorb photons in OSCs [11] or to enable lasing operation of multilayer nanofibers [12]. Exploring and, consequently, exploiting these structure-property relations are thus necessary steps to achieve economically worthwhile device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic processes involved in the stimulated light emission in a semiconductor are also different if an exciton gas or a plasma of unbound electrons and holes are involved, primarily due to the different way to accumulate for population inversion in Bose and Fermi distributions. In organics, an incoherent exciton population is generated following optical excitation; stimulated emission requires the annihilation of an exciton and the generation of a ground state vibration, very similar to a molecular three-level system 32,33 . In inorganic semiconductors, light amplification at room temperature mostly occurs from electron-hole recombination in a conducting plasma.…”
mentioning
confidence: 99%
“…Recently, it has also been demonstrated that the described concept of an alternated deposition of multiple molecular species represents a powerful approach to achieve nanofiber lasing with ultrahigh bandwidth [58]. Based on the p-6P/6T material couple, the wavelength coverage of organic nanofibers' lasing could be extended from the deep blue to the red-orange, and it has been shown that bimolecular recombination can be suppressed.…”
Section: Device Structuresmentioning
confidence: 99%
“…Based on the p-6P/6T material couple, the wavelength coverage of organic nanofibers' lasing could be extended from the deep blue to the red-orange, and it has been shown that bimolecular recombination can be suppressed. excited-state recombination regime can be achieved by periodic organic-organic heteroepitaxy [58]. The first monolayer (ML) of 6T homogeneously covers the p-6P fibers, which becomes visible by green fluorescence.…”
Section: Device Structuresmentioning
confidence: 99%
See 1 more Smart Citation